2021
DOI: 10.1007/s00432-021-03601-x
|View full text |Cite
|
Sign up to set email alerts
|

NLRC5 regulates expression of MHC-I and provides a target for anti-tumor immunity in transmissible cancers

Abstract: Purpose Downregulation of MHC class I (MHC-I) is a common immune evasion strategy of many cancers. Similarly, two allogeneic clonal transmissible cancers have killed thousands of wild Tasmanian devils (Sarcophilus harrisii) and also modulate MHC-I expression to evade anti-cancer and allograft responses. IFNG treatment restores MHC-I expression on devil facial tumor (DFT) cells but is insufficient to control tumor growth. Transcriptional co-activator NLRC5 is a master regulator of MHC-I in humans and mice but i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 108 publications
1
17
0
Order By: Relevance
“…We have previously shown that MHC-I on DFT1 cells is the predominant antibody target in devils with natural and induced anti-DFT immune response including tumour regressions (Ong et al, 2021). Here we tested if expression of CIITA in DFT cells could also upregulate antibody targets on DFT cells.…”
Section: Analysis Of Anti-dft Serum Antibody Response Against Ciita-induced Antigensmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously shown that MHC-I on DFT1 cells is the predominant antibody target in devils with natural and induced anti-DFT immune response including tumour regressions (Ong et al, 2021). Here we tested if expression of CIITA in DFT cells could also upregulate antibody targets on DFT cells.…”
Section: Analysis Of Anti-dft Serum Antibody Response Against Ciita-induced Antigensmentioning
confidence: 97%
“…Serum samples from four devils (My, TD4, TD5, and TD6), collected before (pre-immune) and after DFT1 clinical manifestations (immune), were used to assess antibody responses towards CIITA-expressing DFT cell lines (Supplementary Table 5). The serum samples were identified as immune from the presence of anti-DFT1 antibodies, which were found to be predominantly against MHC-I on DFT1 cells (Ong et al, 2021). 'My' was a devil that was immunised, challenged with DFT1 cells, and subsequently treated with an experimental immunotherapy that induced tumour regression (Tovar et al, 2017).…”
Section: Flow Cytometric Analysis Of Serum Antibody Bindingmentioning
confidence: 99%
“…This occurs via epigenetic downregulation of several components of the MHC-I antigen processing pathway [5] and a hemizygous deletion of beta-2 microglobulin (B2M), which is necessary for stabilizing MHC-I complexes on the cell surface [6]. Natural and immunotherapyinduced tumour regressions have been observed in devils, along with antibody responses to DFT1 cells, albeit primarily in the context of MHC-I [7][8][9]. Conversely, the emerging DFT2 tumours do express MHC-I [10], suggesting that other immune evasion mechanisms are important.…”
Section: Introductionmentioning
confidence: 99%
“…Natural DFT1 regressions have also been observed in wild devils ( Pye et al , 2016 ; Margres et al , 2018 ). CRISPR/Cas9 was used to completely knockout MHC-I from DFT1 cells, and this cell line was used to show that MHC-I proteins are a major serum antibody target in devils that had immunotherapy-induced or natural DFT1 regressions ( Pye et al , 2016 ; Margres et al , 2018 ; Ong et al , 2021 ). Altogether these results suggest that low MHC-I diversity and reduced MHC-I expression are important for transmissible cancer cells, but additional mechanisms are likely employed to evade immune defences.…”
Section: Applied Ecoimmunology In Conservation: Case Studiesmentioning
confidence: 99%